The Effect of Litter Type and Litter Thickness on Broiler Carcass Traits - Demirulus, H. (International Journal of Poultry Science, 2006)
In this research, straw and pine shavings were used as litter. Litter thicknesses were 5, 8 and 11cm respectively. 18 chicks were placed per m2 and total 120 chicks were used in 3 groups. The study was performed two replicates. According to results of the investigation, the best live weight (1.67±0.11 kg) and carcass weight (1135.06±84.47g), heart weight (10.48±1.68g), liver (38.39±5.51g) and gizzard weight (37.10±4.40 g), and carcass yield (67.90±3.2%) were obtained from 5cm-pine shaving group. These results were significantly higher than the results of 11cm-straw and 11cm mixed form. Desired lowest abdominal fat level (17.28±2.6 kg) and feed efficiency rate (2.25) were also obtained from pine shavings of 5 cm thickness